The Impact of High-Energy and High-Protein Bitsoya Snacks on Weight Changes in Underweight Adolescent Girls - Utami, Dita Rahma; Siregar, Afriyana; Podojoyo; Susyani; Muzakar; Sriwiyanti (poltekkes kemenkes mataram, 2025)
Being overweight is a deficient nutritional status due to a lack of nutritional intake entering the body. It is said that a teenager is underweight if the results of the z-score measurement of Body Mass Index According to Age (BMI/U) are -3 SD to <-2 SD. Efforts to prevent nutritional problems related to energy consumption include consuming varied foods containing enough calories and protein. To determine the effect of high-energy and protein Bitsoya snacks on weight changes in South Merapi 1 State Junior High School underweight female adolescents. This type of research is quantitative research with a quasi-experimental design. The research design used a pre-test and post-test with one group. In this study, the average weight gain for respondents was 0.262 kg. The multiple linear regression test results obtained a significant value for the protein intake variable with a p-value of 0.048 (< 0.05). Giving bitsoya (soy stick biscuits) affects the weight gain of underweight adolescent girls.